Integrated transcriptomic analysis identifies lactylation-linked gemcitabine resistance and therapeutic targets in intrahepatic cholangiocarcinoma - Xie, Wenwei; Hu, Jialiang; Xu, Hanmei (Frontiers in Cell and Developmental Biology, 2025)
BackgroundIntrahepatic cholangiocarcinoma (iCCA) is a highly aggressive malignancy of the bile ducts, and resistance to gemcitabine, a first-line chemotherapy, significantly complicates treatment. Despite extensive research, the molecular mechanisms underlying gemcitabine resistance in iCCA are not fully understood. This study aims to identify key genes associated with gemcitabine resistance in iCCA, investigate the role of lactylation, and propose potential therapeutic targets.MethodsA comprehensive bioinformatics analysis was conducted using publicly available transcriptomic data from gemcitabine-resistant iCCA cell lines and patient samples. Differential expression analysis was performed to identify upregulated and downregulated genes. GSEA were used to explore relevant molecular pathways. Immune landscape analysis was carried out using CIBERSORT to assess immune cell infiltration in the tumor microenvironment. Key resistance-related genes were identified through Lasso, RF, and SVM-REF analyses. ITGB4 function was further validated in vitro by siRNA knockdown in HUCCT1 and RBE cells, followed by cell viability and apoptosis assays with or without gemcitabine treatment.ResultsPathway analysis revealed the involvement of cell cycle regulation, DNA replication, and p53 signaling in gemcitabine resistance. The high group associated with resistance showed significantly worse survival outcomes, with a positive correlation between resistance and lactylation levels. Immune landscape analysis indicated altered immune cell infiltration, including increased M2 macrophages and decreased CD8+ T cells in the high group. Key resistance-related genes, including CDC20, H2AX, HK2, and ITGB4, were identified as critical in drug resistance. Experimentally, ITGB4 knockdown markedly enhanced gemcitabine’s antiproliferative and pro-apoptotic effects on cholangiocarcinoma cells, supporting its role in mediating resistance. Molecular docking revealed Dioscin and Deacetyllanatoside C as potential ITGB4-interacting compounds.ConclusionThis study sheds light on the molecular mechanisms of gemcitabine resistance in iCCA, emphasizing lactylation’s role and the significance of immune modulation. ITGB4 is identified as a promising therapeutic target, and the findings suggest that targeting these genes could help overcome resistance in iCCA.